2022
DOI: 10.1002/lno.12044
|View full text |Cite
|
Sign up to set email alerts
|

Transformation processes of biogenic dimethylated sulfur compounds in the northwestern Pacific continental sea

Abstract: Biogenic dimethylated sulfur compounds, comprising dimethylsulfide (DMS), dimethylsulfoniopropionate (DMSP), and dimethylsulfoxide, play a vital role in the physiological metabolism processes of marine algae, climate regulation, and global sulfur cycles, but the contribution of each transformation pathway and the factors that control them remain uncertain. For the first time, from 27 March 2017 to 15 April 2017, the rates of major transformation pathways of biogenic dimethylated sulfur compounds and the fluxes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…UV radiation emerged as the predominant factor (>80%; Figure 2d) driving surface DMS photodegradation, aligning with previous research. 14,15 DMS photodegradation, primarily facilitated by secondary photosensitizers such as CDOM and nitrate, 51,52 occurs more rapidly in high-latitude regions abundant in photosensitizers and lowlatitude regions with intense solar radiation (e.g., Station P27), as evidenced by the rate constants (Table S2). Upon normalization to photon flux density, the KOE displayed the highest DMS photodegradation rate (Table S5), with UVB showing a significantly higher influence (UVB:UVA:PAR ratio of 463:39:1).…”
Section: Loss Processes Of Dms Ocs and Cs 2 331 Microbial Consumptio...mentioning
confidence: 99%
See 1 more Smart Citation
“…UV radiation emerged as the predominant factor (>80%; Figure 2d) driving surface DMS photodegradation, aligning with previous research. 14,15 DMS photodegradation, primarily facilitated by secondary photosensitizers such as CDOM and nitrate, 51,52 occurs more rapidly in high-latitude regions abundant in photosensitizers and lowlatitude regions with intense solar radiation (e.g., Station P27), as evidenced by the rate constants (Table S2). Upon normalization to photon flux density, the KOE displayed the highest DMS photodegradation rate (Table S5), with UVB showing a significantly higher influence (UVB:UVA:PAR ratio of 463:39:1).…”
Section: Loss Processes Of Dms Ocs and Cs 2 331 Microbial Consumptio...mentioning
confidence: 99%
“…It is estimated that approximately 27.1 Tg of sulfur, in the form of DMS, is emitted from the ocean annually . Besides, sea surface DMS can be removed through microbial metabolism and photo-oxidation. , OCS is generally produced via reactions between ultraviolet radiation and dissolved organic sulfur, which is an indirect process photosensitized by chromophoric dissolved organic matter (CDOM). The reaction of sulfur radicals can also produce OCS in the dark.…”
Section: Introductionmentioning
confidence: 99%
“…DMS-loss processes involve microbial consumption, photochemical oxidation, ventilation to the atmosphere, and vertical export by mixing in the euphotic layer. DMS consumption by bacteria is generally the major loss process, accounting for 50%-80% of the total, whereas release to the atmosphere represents only a small proportion of total DMS removal Simo, 2004;Toole et al, 2006;Vila-Costa et al, 2008;Ma et al, 2022). The amount of DMS released to the atmosphere accounts for only 3% of the total DMSP in the ocean (Kiene and Service, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Spatially, the summertime [DMS] exhibits a patchy characteristic with higher value occurring in the Changjiang estuary and its adjacent area, and Zhejiang coastal (Ma & Yang, 2023b; Yang et al., 2011; Zhu et al., 2019) and, a significant positive correlation is found between [DMS] and total chlorophyll a concentration ([Chl a ]) in the YECS (Gao et al., 2017; Jian et al., 2018; Yang et al., 2011). Some studies have focused on the effect of seawater acidification and nutrient inputs on the DMS cycle (Gao et al., 2021; Jian et al., 2019; Ma & Yang, 2023a). Ship‐based incubation experiments revealed that the increased [DMS] was substantially ascribed to the elevated phytoplankton biomass that response to these environmental changes (Ma & Yang, 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on the effect of seawater acidification and nutrient inputs on the DMS cycle (Gao et al., 2021; Jian et al., 2019; Ma & Yang, 2023a). Ship‐based incubation experiments revealed that the increased [DMS] was substantially ascribed to the elevated phytoplankton biomass that response to these environmental changes (Ma & Yang, 2023a). Totally, the response of biogenic DMS emitted from the YECS to environmental changes is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%